HUBUNGAN MOTIVASI BELAJAR MAHASISWA DALAM AKTIVITAS PRAKTIKUM BIOTEKNOLOGI TERHADAP HASIL BELAJAR PSIKOMOTOR MAHASISWA PENDIDIKAN IPA BIOLOGI UNISBA - Dian Puspita Anggraini (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2015)
The objectives of this study are to see: (1) students ’ motivation on the practicum of sciences in the subject of biotechnology, (2) psychomotor learning outcomes in the practicum, and (3) an evidence whether learning motivation relates to the psychomotor learning outcomes. This study used correlation design and assigned the first semester 40 students of Biology Department at Balitar Islamic University in the year 2015/2016. Data were analyzed using product moment analysis. This study discovered that a .623 correlational point was achieved in the analysis, indicating that positive relation exists between learning motivation in the practicum activities and psychomotor learning outcomes.